Film for enhancing polarization and energy storage characteristics based on negative capacitance effect and preparation method
By designing a multi-layer heterogeneous antiferroelectric film structure and utilizing the negative capacitance effect and alternating deposition technology, the problem of high energy storage density and low operating voltage in antiferroelectric energy storage capacitors is solved, and high energy storage is achieved. Density, high energy storage efficiency and long service life.
Patent Information
- Application Number
- CN202411373235.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-09-29
AI Technical Summary
The existing antiferroelectric energy storage capacitors are difficult to take into account between high energy storage density and low operating voltage, and the large hysteresis width of the antiferroelectric body leads to low energy storage efficiency.
Design a multi -layer heresy anti -iron film structure based on negative capacitance effects. Through alternating PBZRO3 and PLZS film, optimize the polarized charge transfer of the dielectric layer, break the long -range order of the anti -iron electricity, and obtain the "narrow and obliqueness "Electric stagnation line.
It improves energy storage density, energy storage efficiency and service life, and solves the problem of low energy storage efficiency of anti -iron electrical electrical stagnation, which meets the needs of miniaturization and low working voltage.
Smart Images

Figure CN119340113A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of semiconductor devices, and in particular to a film with enhanced polarization and energy storage characteristics based on negative capacitance effect and a preparation method thereof. Background Art
[0002] Compared with electrochemical capacitors and batteries, dielectric capacitors have ultra-high power density (10 8 W / kg) and ultra-fast charge-discharge capabilities (microseconds or even nanoseconds), and this energy conversion process is a physical process, without involving mass transfer and oxidation-reduction reactions, which can effectively avoid risks such as leakage and explosion, and is safer and more durable. Although dielectric energy storage capacitors have been widely used, they are limited by the small energy storage density. In general power electronics and pulse power systems, capacitors account for 23% and 40% of the total volume and weight, respectively. With the rapid development of electronic technology and devices, miniaturization and integration have become the future development direction of dielectric capacitors. Therefore, the development of energy storage capacitors with high energy density, high efficiency and long service life has become the current research focus in the field of pulse power technology.
[0003] The materials currently studied in dielectric energy storage can be divided into the following categories: (1) Linear dielectrics: The polarization intensity is linearly related to the electric field intensity. The dielectric constant is usually very small and hardly changes with the electric field intensity. It has good stability in an environment with voltage, temperature, and frequency changes. The main disadvantage is that the polarization intensity is not high. (2) Ferroelectrics: They usually have a high dielectric constant, but conventional ferroelectrics have a large residual polarization intensity, showing large energy loss and low energy storage efficiency. (3) Relaxor ferroelectrics: They have a "thin" hysteresis loop and show high energy storage efficiency. , this type of material needs to obtain a large energy storage density under a large voltage excitation, which obviously does not meet the requirements of device integration and miniaturization for lower operating voltage; (4) Antiferroelectrics: According to the lattice dynamics soft mode theory, under the action of an external electric field, the essence of the antiferroelectric / ferroelectric phase transition is the result of the competition between short-range forces and long-range forces. Its energy storage principle is essentially to use the external field to induce the antiferroelectric-ferroelectric phase transition to complete the storage and release of energy. Antiferroelectrics have double hysteresis loops and smaller residual polarization intensity, and theoretically have a larger energy storage density.
[0004] At present, domestic and foreign researchers have adopted a variety of research methods to improve energy storage properties, including: optimizing the synthesis process to improve density, constructing core-shell structure, introducing large bandgap materials, constructing polymorphic nanodomains, linear dielectrics (or relaxor ferroelectrics) + ferroelectric composites, etc. However, the essence of the above methods is to obtain high energy storage density by increasing the breakdown electric field. According to the dielectric energy storage calculation formula: J reco=∫EdP, where E and P are the electric field strength and polarization strength, respectively. Improving the breakdown electric field is certainly one of the effective means to increase the energy storage density, but a large electric field is accompanied by a large strain. It has been reported in the literature that the electrostrain of antiferroelectric films can be as high as 1% or more, which is not conducive to the service life. Unfortunately, there are few reports on the damage to the service life of devices caused by the strain effect brought by large electric fields. With the development trend of device miniaturization and high power, the demand for device operating voltage is getting lower and lower. Therefore, it is not an ideal means to obtain high energy storage density by improving the breakdown strength.
[0005] The optimal working electric field of the antiferroelectric energy storage capacitor should be selected near the antiferroelectric-ferroelectric phase transition electric field. By increasing the polarization intensity near the antiferroelectric-ferroelectric phase transition electric field to obtain a large energy storage density, it not only effectively avoids the service life problem caused by the large electric field, but also meets the requirements of miniaturization for low working voltage. It is worth noting that although antiferroelectrics theoretically have a large energy storage density, their large hysteresis width causes the energy storage efficiency to be mostly less than 90%. Low energy storage efficiency is a common problem of antiferroelectric energy storage. Summary of the invention
[0006] In order to solve the above technical problems existing in the prior art, the embodiment of the present invention provides a film and a preparation method for enhancing polarization and energy storage characteristics based on the negative capacitance effect. The technical solution is as follows:
[0007] On the one hand, a film with enhanced polarization and energy storage properties based on negative capacitance effect is provided, comprising: a substrate, a bottom electrode layer and a top electrode layer, wherein the bottom electrode layer is deposited on the surface of the substrate, and multiple layers of first antiferroelectric layers and second antiferroelectric layers are alternately deposited between the bottom electrode layer and the top electrode layer; wherein the material of the first antiferroelectric layer comprises a PbZrO3 film; and the material of the second antiferroelectric layer comprises a PLZS film.
[0008] Furthermore, the chemical formula of the PLZS film includes: Pb 0.97 La 0.02 Zr 0.55 Sn 0.45 O3.
[0009] Furthermore, the material of the substrate includes SrTiO3; the material of the bottom electrode layer includes SrRuO3; and the material of the top electrode layer includes Pt.
[0010] Furthermore, the thickness of the bottom electrode layer is greater than 10 nm; the thickness of the top electrode layer is 50 nm; and the thickness of the first antiferroelectric layer or the second antiferroelectric layer is greater than 20 nm.
[0011] On the other hand, a method for preparing a film with enhanced polarization and energy storage characteristics based on the negative capacitance effect is also provided, comprising: attaching the substrate to a heating support, and depositing the bottom electrode layer on the substrate by a pulsed laser deposition coating method; repeatedly growing the first antiferroelectric layer and the second antiferroelectric layer alternately on the bottom electrode layer by a pulsed laser deposition coating method to form a multilayer heterogeneous antiferroelectric film structure; and coating the top electrode layer on the topmost layer of the multilayer heterogeneous antiferroelectric film structure based on a photolithography method.
[0012] Furthermore, the substrate is attached to a heating support, and the bottom electrode layer is deposited on the substrate by a pulsed laser deposition coating method, including: attaching a (001) oriented SrTiO3 substrate to a heating support with silver glue, and then heating to 150-170°C to cure the resin for 10 minutes; placing the heating support into a PLD cavity, and evacuating to 10 -3 Pa, and then rapidly heated to 680°C at a heating rate of 10-15°C / min, the oxygen pressure inside the cavity was adjusted to 13Pa, and SrRuO3 was deposited in an oxygen atmosphere to form the bottom electrode layer.
[0013] Furthermore, a pulsed laser deposition coating method is used to repeatedly and alternately grow the first antiferroelectric layer and the second antiferroelectric layer on the bottom electrode layer to form a multilayer heterogeneous antiferroelectric thin film structure, including: switching the PLD cavity temperature to 590°C, and adjusting the oxygen pressure inside the PLD cavity to 11Pa; switching the target material to PbZrO3 to deposit a PZO film on the bottom electrode layer to form the first antiferroelectric layer; then switching to a PLZS target material to deposit a PLZS film to form the second antiferroelectric layer; repeatedly and alternately growing the first antiferroelectric layer and the second antiferroelectric layer to form the multilayer heterogeneous antiferroelectric thin film structure; finally cooling at a rate of 5°C / min, and annealing in a high-pressure oxygen atmosphere.
[0014] Furthermore, based on the photolithography method, the top electrode layer is plated on the top layer of the multi-layer heterogeneous antiferroelectric thin film structure, including: transferring the pattern of the top electrode by photolithography, using magnetron sputtering to plate a layer of Pt as the top electrode layer on the top layer of the multi-layer heterogeneous antiferroelectric thin film structure, and finally removing the photoresist by a wet method.
[0015] The embodiment of the present invention provides a film and a preparation method for enhancing polarization and energy storage characteristics based on the negative capacitance effect, designs a multilayer heterogeneous antiferroelectric film structure, and from the perspective of stable polarization charge transfer in the dielectric layer, breaks the long-range order of antiferroelectricity by optimizing the multilayer antiferroelectric film structure, obtains a "narrow oblique" hysteresis loop with relaxation characteristics, and simultaneously utilizes the antiferroelectric "negative capacitance effect" to improve the dielectric constant and polarization strength, and finally obtains a "narrow oblique" hysteresis loop with a large polarization strength, which can simultaneously improve the energy storage density, energy storage efficiency and service life, and alleviates the technical problem of low energy storage efficiency caused by the large hysteresis width of antiferroelectrics in the prior art. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0017] Figure 1 It is a schematic structural diagram of a film for enhancing polarization and energy storage characteristics based on negative capacitance effect provided by an embodiment of the present invention;
[0018] Figure 2 A method for preparing a thin film with enhanced polarization and energy storage properties based on negative capacitance effect is provided in an embodiment of the present invention;
[0019] Figure 3 It is a schematic diagram of an electrical performance test of a film with enhanced polarization and energy storage characteristics based on negative capacitance effect provided by an embodiment of the present invention;
[0020] Figure 4 This is an XRD diagram of a PZO / PLZS multilayer film provided by an embodiment of the present invention;
[0021] Figure 5 is an AFM image of a PZO / PLZS multilayer film provided according to an embodiment of the present invention;
[0022] Figure 6 This is a PZO / PLZS multilayer film dielectric spectrum diagram provided by an embodiment of the present invention;
[0023] Figure 7 It is a PZO / PLZS multilayer thin film ferroelectric loop and energy storage result diagram provided by an embodiment of the present invention. DETAILED DESCRIPTION
[0024] The technical solution of the present invention is described below in conjunction with the accompanying drawings.
[0025] In the embodiments of the present invention, words such as "exemplarily" and "for example" are used to indicate examples, illustrations or explanations. Any embodiment or design described as "example" in the present invention should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of the word "example" is intended to present the concept in a specific way. In addition, in the embodiments of the present invention, the meaning expressed by "and / or" can be both, or it can be either of the two.
[0026] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0027] Embodiment 1
[0028] Figure 1 Schematic diagram of a film structure based on a negative capacitance effect to enhance polarization and energy storage characteristics according to an embodiment of the present invention. Figure 1 As shown, the structure of the film includes: a substrate 1, a bottom electrode layer 2 and a top electrode layer 3. The bottom electrode layer 2 is deposited on the surface of the substrate 1, and multiple layers of first antiferroelectric layers 4 and second antiferroelectric layers 5 are alternately deposited between the bottom electrode layer 2 and the top electrode layer 3.
[0029] Specifically, the material of the first antiferroelectric layer 4 includes a PbZrO3 thin film;
[0030] The material of the second antiferroelectric layer 5 includes a PLZS thin film.
[0031] In an optional implementation provided by an embodiment of the present invention, the chemical formula of the PLZS film includes: Pb 0.97 La 0.02 Zr 0.55 Sn 0.45 O3.
[0032] Preferably, in an embodiment of the present invention, the material of the substrate includes SrTiO3 (STO);
[0033] The materials of the bottom electrode layer include: SrRuO3 (SRO);
[0034] The material of the top electrode layer includes Pt.
[0035] In an optional implementation provided by an embodiment of the present invention, the thickness of the bottom electrode layer is greater than 10 nm; the thickness of the top electrode layer is 50 nm; and the thickness of the first antiferroelectric layer or the second antiferroelectric layer is greater than 20 nm.
[0036] Embodiment 2
[0037] Figure 2 A method for preparing a thin film with enhanced polarization and energy storage properties based on negative capacitance effect is provided according to an embodiment of the present invention. Figure 2As shown, the method specifically comprises the following steps:
[0038] Step S202, attaching the substrate to the heating support, and depositing a bottom electrode layer on the substrate using a pulsed laser deposition coating method.
[0039] Step S204, using a pulsed laser deposition coating method, repeatedly and alternately growing a first antiferroelectric layer and a second antiferroelectric layer on the bottom electrode layer to form a multi-layer heterogeneous antiferroelectric thin film structure.
[0040] Step S206: Based on the photolithography method, a top electrode layer is plated on the top layer of the multi-layer heterogeneous antiferroelectric thin film structure.
[0041] The pulsed laser deposition (PLD) method used in the thin film preparation method provided in the embodiment of the present invention is a physical vapor deposition technology for high-quality thin film epitaxial growth. It uses laser to bombard the target material, and deposits the bombarded plasma on the substrate to achieve epitaxial growth of the thin film. Compared with the sol-gel method, chemical solution deposition method, atomic layer deposition method, etc., PLD can perform uniform coating on composite materials with complex chemical compositions, and it is easy to ensure the stability of the stoichiometric ratio after coating, and can obtain a multi-component thin film with a desired stoichiometric ratio, that is, it has good composition retention characteristics.
[0042] Specifically, step S202 also includes the following steps:
[0043] Step S2021, attach the (001) oriented SrTiO3 substrate to the heating support with silver glue, and then heat to 150-170°C to cure the resin for 10 minutes;
[0044] Step S2022, place the heating tray into the PLD chamber and evacuate to 10 -3 Pa, and then rapidly heated to 680°C at a heating rate of 10-15°C / min, the oxygen pressure inside the cavity was adjusted to 13Pa, and SrRuO3 was deposited in an oxygen atmosphere to form a bottom electrode layer.
[0045] In the embodiment of the present invention, in order to continue to grow multilayer films, the SRO thickness is required to be greater than 10 nm and have good conductivity, and the SRO surface is flat (Rq<0.5 nm) to ensure subsequent high-quality epitaxial growth of multilayer films.
[0046] Specifically, step S204 also includes the following steps:
[0047] Step S2041, switching the PLD chamber temperature to 590°C and adjusting the oxygen pressure inside the PLD chamber to 11Pa;
[0048] Step S2042, switching the target material to PbZrO3 to deposit a PZO film on the bottom electrode layer to form a first antiferroelectric layer; in the embodiment of the present invention, considering the size effect of the antiferroelectric, the thickness of the single-layer PZO film is greater than 20 nm;
[0049] Step S2043, then switch to the PLZS target material to deposit a PLZS thin film to form a second antiferroelectric layer;
[0050] Step S2044, repeatedly and alternately growing the first antiferroelectric layer and the second antiferroelectric layer to form a multi-layer heterogeneous antiferroelectric thin film structure;
[0051] Step S2045, finally cooling at a rate of 5°C / min and annealing in a high-pressure oxygen atmosphere. Preferably, the pressure of the high-pressure oxygen atmosphere is 10000Pa.
[0052] Specifically, step S206 also includes the following steps: transferring the pattern of the top electrode by photolithography, coating the top layer of the multi-layer heterogeneous antiferroelectric thin film structure with a layer of Pt as a top electrode layer by magnetron sputtering, and finally removing the photoresist by wet method.
[0053] Embodiment 3
[0054] Figure 3 Schematic diagram of electrical performance test of a film based on negative capacitance effect to enhance polarization and energy storage characteristics according to an embodiment of the present invention. Figure 3 The structure shown in the figure is used to test the electrical performance of the film based on the negative capacitance effect to enhance the polarization and energy storage characteristics provided by the embodiment of the present invention. The test results are as follows:
[0055] Figure 4 is an XRD diagram of a PZO / PLZS multilayer film provided according to an embodiment of the present invention, Figure 5 1 is an AFM image of a PZO / PLZS multilayer film provided according to an embodiment of the present invention. Figure 4 and Figure 5 As shown, the film based on the negative capacitance effect to enhance polarization and energy storage characteristics provided by the embodiment of the present invention has good crystallinity and no impurity peaks (such as Figure 4 As shown in Figure 2, the surface of the multilayer film is atomically flat, with a roughness of <0.6nm (as shown in Figure 2). Figure 5 as shown).
[0056] Figure 6 This is a PZO / PLZS multilayer film dielectric spectrum diagram provided according to an embodiment of the present invention. Figure 7 1 is a PZO / PLZS multilayer thin film ferroelectric loop and energy storage result diagram provided according to an embodiment of the present invention. Figure 6 and Figure 7As shown, the film based on the negative capacitance effect to enhance polarization and energy storage characteristics provided by the embodiment of the present invention can greatly improve the dielectric constant (such as Figure 6 ) and polarization intensity (as Figure 7 The increase in polarization strength will help increase the energy storage density (by nearly 4 times).
[0057] From the above description, it can be seen that the embodiment of the present invention provides a film and a preparation method based on the negative capacitance effect to enhance the polarization and energy storage characteristics, and utilizes the superposition effect of the antiferroelectric "negative capacitance effect" and the capacitance (dielectric constant) after the conventional linear dielectric is connected in series to design a multilayer heterogeneous antiferroelectric film (PbZrO3 / Pb 0.97 La 0.02 Zr 0.55 Sn 0.45 O3, abbreviated as PZO / PLZS) structure, which improves the dielectric constant of the capacitor and obtains large polarization strength and high energy storage density.
[0058] It should be understood that in various embodiments of the present invention, the size of the serial numbers of the above-mentioned processes does not mean the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present invention.
[0059] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A film with enhanced polarization and energy storage properties based on negative capacitance effect, characterized in that: include: A substrate, a bottom electrode layer and a top electrode layer, wherein the bottom electrode layer is deposited on the surface of the substrate, and multiple layers of first antiferroelectric layers and second antiferroelectric layers are alternately deposited between the bottom electrode layer and the top electrode layer; wherein: The material of the first antiferroelectric layer includes a PbZrO3 thin film; The material of the second antiferroelectric layer includes a PLZS thin film.
2. The film according to claim 1, characterized in that: The chemical formula of the PLZS film includes: Pb 0.97 La 0.02 Zr 0.55 Sn 0.45 O3.
3. The film according to claim 1, characterized in that: The material of the substrate includes SrTiO3; The material of the bottom electrode layer includes: SrRuO3; The material of the top electrode layer includes Pt.
4. The film according to claim 1, characterized in that: The thickness of the bottom electrode layer is greater than 10 nm; the thickness of the top electrode layer is 50 nm; the thickness of the first antiferroelectric layer or the second antiferroelectric layer is greater than 20 nm.
5. A method for preparing a film having enhanced polarization and energy storage properties based on negative capacitance effect as claimed in claim 1, characterized in that: include: The substrate is attached to a heating support, and the bottom electrode layer is deposited on the substrate by a pulsed laser deposition coating method; Using a pulsed laser deposition coating method, repeatedly and alternately growing the first antiferroelectric layer and the second antiferroelectric layer on the bottom electrode layer to form a multi-layer heterogeneous antiferroelectric thin film structure; Based on the photolithography method, the top electrode layer is plated on the uppermost layer of the multi-layer heterogeneous antiferroelectric thin film structure.
6. The method according to claim 5, characterized in that The substrate is attached to a heating support, and the bottom electrode layer is deposited on the substrate by a pulsed laser deposition coating method, including: The (001) oriented SrTiO3 substrate was attached to the heating support with silver glue, and then heated to 150-170°C to cure the resin for 10 min; Place the heating tray into the PLD chamber and evacuate to 10 -3 Pa, and then rapidly heated to 680°C at a heating rate of 10-15°C / min, the oxygen pressure inside the cavity was adjusted to 13Pa, and SrRuO3 was deposited in an oxygen atmosphere to form the bottom electrode layer.
7. The method according to claim 5, characterized in that The first antiferroelectric layer and the second antiferroelectric layer are repeatedly and alternately grown on the bottom electrode layer by using a pulsed laser deposition coating method to form a multilayer heterogeneous antiferroelectric thin film structure, including: The PLD chamber temperature was switched to 590°C and the oxygen pressure inside the PLD chamber was adjusted to 11Pa; Switching the target material to PbZrO3, depositing a PZO thin film on the bottom electrode layer to form the first antiferroelectric layer; Then, the PLZS target is switched to deposit a PLZS thin film to form the second antiferroelectric layer; Repeatedly and alternately growing the first antiferroelectric layer and the second antiferroelectric layer multiple times to form the multi-layer heterogeneous antiferroelectric thin film structure; Finally, the temperature was lowered at a rate of 5°C / min and annealed in a high-pressure oxygen atmosphere.
8. The method according to claim 5, characterized in that Based on the photolithography method, the top electrode layer is plated on the top layer of the multi-layer heterogeneous antiferroelectric thin film structure, comprising: The pattern of the top electrode is transferred by photolithography, a Pt layer is plated on the top layer of the multi-layer heterogeneous antiferroelectric thin film structure as the top electrode layer by magnetron sputtering, and finally the photoresist is removed by wet method.
Citation Information
Patent Citations
High-energy storage density antiferroelectric thick membrane and preparation method thereof
CN108314443A
Lead lanthanum zirconate stannate antiferroelectric ceramic as well as preparation method and application thereof
CN111393149A
Semiconductor device
CN113690226A
Antiferroelectric multilayer ceramic capacitor
US20090207555A1
Semiconductor device
US20210359082A1